Constructing secure mobile agent systems using the agent operating system. (17th December 2009) - Van 't Noordende, Guido J.; Overeinder, Benno J.; Timmer, Reinier J.; Brazier, Frances M.T.; , Andrew S. Tanenbaum
Designing a secure and reliable mobile agent system is a difficult task. The agent operating system (AOS) is a building block that simplifies this task. AOS provides common primitives required by most mobile agent middleware systems, such as primitives for secure communication, secure and tamper-evident agent packaging and agent migration. Different middleware processes can use AOS at the same time; effective security mechanisms protect AOS resources owned by different middleware processes. Designed as a portable and language-neutral middleware layer residing between the mobile agent system and the operating system, AOS facilitates interoperability between agent platforms and between different implementations of AOS itself. AOS has been implemented in both C++ and Java. This paper motivates the design of AOS, describes how AOS is used in a mobile agent system, and presents performance measures for an agent transfer protocol layered upon AOS.